0
$\begingroup$

I divided the time interval $[t_0=:t_i,t_f:=t_N]$ into $N$ steps $[t_{k-1},t_{k}],\, k=1,\dots, N$ and applied the resolution of unity for coherent states \begin{equation} \mathbb{I}=\int_\mathbb{C}\frac{dzd\bar{z}}{2\pi i}\exp\left\lbrace-z\bar{z}\right\rbrace\lvert z\rangle\langle z\rvert \end{equation} at each step; this yields the following \begin{multline} \langle{z_f}\lvert\left( \exp\lbrace-iH\epsilon\right\rbrace)^N\rvert z_i\rangle=\dots=\lim_{N\to\infty}\int\prod_{j=1}^{N-1}\frac{dz_jd\bar{z_j}}{2\pi i}\\ \exp\left\lbrace\sum_{k=0}^{N-1}\bar{z}_{k+1}z_k-\sum_{k=1}^{N-1}z_k\bar{z_k}-i\epsilon\sum_{k=0}^{N-1}H(\bar{z}_{k+1},z_k)\right\rbrace,\quad(*) \end{multline} where $\epsilon:=\frac{t_f-t_i}{N}$, and with boundary conditions $z_0=z_i,\,\bar{z}_N=\bar{z}_f$. Then I need to put $(*)$ in this form \begin{align} \int\mathcal{D}(z,\bar{z})&\exp\bigg\lbrace\frac{\bar{z}_fz_f+\bar{z}_iz_i}{2}+\frac{1}{2}\sum_{k=0}^{N-1}\big[z_k(\bar{z}_{k+1}-\bar{z}_k)-\bar{z}_k(z_{k+1}-z_k)+\\ &-i\epsilon H(\bar{z}_{k+1},z_k)\big]\bigg\rbrace \end{align} but I can't understand how to transform the argument of the exponential.

Any ideas?

Thanks

Source: Itzykson - Zuber, page 438 with line 2 corrected as shown in the errata (you can find it here: http://www.lpthe.jussieu.fr/~zuber/corrize.pdf).

edit: @ ACuriousMind Then I don't understand how to rewrite it: is the following right? \begin{equation} \frac{1}{2}\sum_{k=0}^{N-1}\big[z_k(\bar{z}_{k+1}-\bar{z}_k)-\bar{z}_k(z_{k+1}-z_k)\big]=\frac{1}{2}\sum_{k=0}^{N-1}\big[z_k\bar{z}_{k+1}-\bar{z}_k z_{k+1}\big]=\sum_{k=0}^{N-1}\big[z_k\bar{z}_{k+1}\big] \end{equation} if this were right, I wouldn't know how to cope with this \begin{equation} -\sum_{k=1}^{N-1}z_k\bar{z}_k \end{equation}

If it is so straightforward to you, could you please rewrite it step-by-step?

$\endgroup$
  • $\begingroup$ It's just a rewriting of the sums, there's no "transformation" required. $\endgroup$ – ACuriousMind Jan 15 '16 at 18:26
  • $\begingroup$ Related: physics.stackexchange.com/q/210138/2451 $\endgroup$ – Qmechanic Jan 15 '16 at 20:00
  • $\begingroup$ @Qmechanic My doubt is not about the path integral itself... it's not obvious to me how to rewrite it in the symmetric form proposed by Itzykson - Zuber... Brown's form of coherent state path integral, which you cite, is slightly different, thus, it doesn't answer my question... $\endgroup$ – Red Lex Jan 15 '16 at 20:09
  • $\begingroup$ Hint: The sought-for manipulation of the action is a discrete version of changing $\lambda=0$ to $\lambda=\frac{1}{2}$ in eq. (7) in my Phys.SE answer here. $\endgroup$ – Qmechanic Jan 15 '16 at 20:41
  • $\begingroup$ You're right... but there is no derivation of that formula in your post. Can you provide a reference? $\endgroup$ – Red Lex Jan 15 '16 at 20:49
1
$\begingroup$

At last I think I managed to rearrange the terms in the sums... (which wasn't a monumental task after all ;-) ) \begin{equation} \sum_{k=0}^{N-1}\bar{z}_{k+1}z_k-\sum_{k=1}^{N-1}z_k\bar{z}_k=(*) \end{equation} In the notation here:

  • $\lambda=0$: \begin{equation} (*)=\sum_{k=0}^{N-1}\bar{z}_{k+1}z_k-\sum_{k=0}^{N-1}z_{k+1}\bar{z}_{k+1}+z_N\bar{z}_N=-\sum_{k=0}^{N-1}\bar{z}_{k+1}(z_{k+1}-z_k)+z_f\bar{z}_f,\,(1) \end{equation}
  • $\lambda=1$: \begin{equation} (*)=\sum_{k=0}^{N-1}\bar{z}_{k+1}z_k-\sum_{k=0}^{N-1}z_k\bar{z}_k+z_0\bar{z}_0=\sum_{k=0}^{N-1}z_k(\bar{z}_{k+1}-\bar{z}_k)+z_i\bar{z}_i,\,(2) \end{equation} Taking $(2)+(1)$ we obtain $2(*)$, and finally
  • $\lambda=1/2$ \begin{equation} \sum_{k=0}^{N-1}\bar{z}_{k+1}z_k-\sum_{k=1}^{N-1}z_k\bar{z}_k=\frac{1}{2}\sum_{k=0}^{N-1}\big[z_k(\bar{z}_{k+1}-\bar{z}_k)-\bar{z}_{k+1}(z_{k+1}-z_k)\big]+\frac{z_i\bar{z}_i+z_f\bar{z}_f}{2} \end{equation} but there was a $+1$ missing in one of the $z$'s subscripts, if I'm right.
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.